ASPEK HUKUM PENUNDAAN KREDIT PERBANKAN AKIBAT PANDEMI COVID-19 DALAM SYSTEM PERBANKAN INDONESIA : (STUDI BANK BRI CABANG CAKRANEGARA) - I Gusti Ayu Marchelia Yusa; Lalu Wira Pria Suhartana; I Gusti Agung Wisudawan (Commerce Law, 2021)
The purpose of this study is to find out and explain the basis for providing banking credit in Indonesia and the legal aspects of delaying banking credit due to the Covid-19 pandemic. The research advantage isas recommendations for readers, academics, and the government. This research is normative and empirical legal research. The research results show that, the legal basis for providing bank credit to customers is based on the duties and obligations of banks as financial institutions in Indonesia, the regulations are: (a) Article 23 and 27 of the 1945 Constitution, (b) Article 1 number 2 of the Banking Law, and (c) the Indonesian Civil Code. Legal protection given to Bank Rakyat Indonesia (BRI) customers due to a credit delay as recommended by the Government are preventive and repressive legal protection measures.